Relationship between p53 protein and ER, PR status in breast cancer tissue - Zhang, Fang (Cancer treatment and research communications, 2025)
•The relationship between the expression level of p53 protein and the status of the estrogen receptor (ER) and progesterone receptor (PR) in breast cancer tissue was studied through experiments.•The analysis of experimental results revealed the intrinsic relationship between p53 protein and status of ER and PR.•The clinical application value of molecular markers p53 protein, ER, and PR were analyzed and elaborated.•It provides a useful reference for further research on the relationship between p53 protein, ER and PR in breast cancer tissue. The aim of the present study was to investigate the protein expression levels of p53 in breast cancer tissues and analyze the relationship between the increased protein expression levels of p53 and the status of the estrogen receptor (ER) and progesterone receptor (PR). A total of 137 patients with breast cancer admitted to the General Surgery Department of the People's Liberation Army General Hospital from June to October 2023 were selected for inclusion in the present study and the expression levels of p53, ER and PR in cancer tissues were detected using immunohistochemistry. According to postoperative pathological results, patients were divided into ER positive negative groups and PR positive negative groups. Chi-squared tests used to analyze the difference in the protein expression levels of p53 between the ER positive and negative groups and the PR positive and negative groups. Additionally, the relationship between the protein expression levels of p53 in breast cancer tissue with patient age, the longest tumor diameter, tumor TNM stage, axillary lymph node status and histological subtype were analyzed. The protein expression levels of p53 in the ER positive and negative groups was 38.27 and 66.07 %, respectively, and the difference was statistically significant.The protein expression levels of p53 in the PR positive and negative groups was 42.27 and 67.50 %, respectively, and the difference was statistically significant. The protein expression levels of p53 in breast cancer tissue was not significantly associated with patient age, the longest tumor diameter, tumor TNM stage and histological subtype. But it was related to the status of axillary lymph nodes, the difference was statistically significant. In conclusion, the protein expression levels of p53 in breast cancer tissues were negatively correlated with the expression of ER and PR, which could be used to potentially provide clinical guidance for the prognosis of patients with breast cancer and improve the diagnosis and treatment of these patients in the future.